Technology acceptance determinants and consumer innovativeness influence on ASNAFS’ acceptance towards the use of e-wallet - Imran Mehboob Shaikh; Hanudin Amin (Emerald Group Publishing Ltd., 2024)
Purpose – This paper aims to examine the determinants that influence acceptance towards e-wallet apps by extending the technology acceptance model (TAM) among (asnaf), a term used for charity or gift receivers from alms tax distribution institutions also known as donee. Design/methodology/approach – The review of literature and structural equation modelling approach using judgemental sampling on extended TAM and determinants of e-wallet apps’ acceptance related to asnaf (donee) were conducted in a bid to contribute to the factors that are instrumental in determining acceptance of e-wallet services among asnaf. Findings – The findings indicate that the e-wallet app’s service acceptance is determined not only by perceived usefulness, consumer maqasid index and consumer innovativeness but also by subjective norms. On the contrary, consumer maqasid index and perceived ease of use do not lend themselves to be the factor of asnafs’ e-wallet acceptance. The authors extend the TAM model to determine the factors that may be influential in predicting the e-wallet app acceptance by asnaf. Research limitations/implications – In assessing future outcomes when different sampling techniques are opted for and geographic coverage is expanded, this study should be considered in terms of the limited scope. Practical implications – This study is intended to serve as a reference for making a significant contribution related to user acceptance factors related to alms tax-based e-wallet apps in asnafs’ context in Malaysia in terms of both theory and practice. Originality/value – TAM is extended in the context of e-wallet app acceptance among asnafs’. A variable, namely, consumer innovativeness, is tested using the extended TAM model. To the best of the authors’ knowledge, consumer innovativeness in the context of asnafs’ acceptance of e-wallet apps is yet to be tested. Therefore, this paper will be a useful reference for policymakers, technologists, academicians and future researchers.